The Use of Smartphone as A Technology-Based Intervention on Managing Nutrition among The Obese Population: A Literature Review - Arifin, Rani Fitriani; Nallappan, Devi (Qualitative and Quantitative Research Center, 2023)
Smartphone apps have been used to promote healthy eating and weight management, as they offer low costs, reduce burdens, and overcome the limitations of traditional in-person programs. The aim of this research is to determine the use of smartphones as a technology-based intervention on managing nutrition. The review method focuses on the relationship between smartphones and healthy diet and nutrition, analyzing 178 articles published up to 2023. The review identified three qualitative studies and five randomized controlled trials investigating the effectiveness and acceptability of smartphone apps for promoting healthy eating and weight management. The results show that a study on the effectiveness of smartphone applications in promoting healthy eating and weight management found that middle-aged men in Australia support using the Internet for improving dietary habits and physical activity, as long as the interventions are user-friendly and efficient . However, they show low commitment to online activities and reluctance to use regular mobile phones for health behavior modification. The study also found that smartphone apps can be effective in promoting healthy eating and weight loss, making them a potentially valuable and cost-effective tool for improving dietary habits, nutrition, and combating obesity. In conclusion, Smartphone applications could serve as an effective and affordable method for improving dietary habits and tackling obesity among the general public. Measurements of diet and nutrition taken through mobile devices are often accurate. The contribution of this research is to increase smartphone users' knowledge to help in monitoring their food consumption and managing their weight.